Pemanfaatan Teknologi Digital dalam Pembelajaran Bahasa Indonesia - Amalia, Agnes Dwi; Wirawati, Denik (Universitas Suryakanca, 2023)
The use of digital technology in the Indonesian language teaching and learning process has become something relatively common nowadays. This article will describe the utilization, usage, and learning outcomes of digital technology in Class XI Indonesian language learning at SMA Muhammadiyah Al Mujahidin Wonosari. This type of research is descriptive qualitative. The subjects of this research are Indonesian language teachers and students. Data collection techniques include interviews, observation, questionnaires, and documentation studies. The instrument of this research is the researcher. The results of this research are (1) the use of digital technology is applied in learning, especially in scientific work material and reviews, starting from giving trigger questions, and delivering the material, to assignments and daily assessments (2) the technology used in delivering the material is the WhatsApp group, Mentimeter, YouTube, PowerPoint (PPT), Google Forms, Portable Document Format (PDF), Internet, Microsoft Word, and Random Team Generator (3) learning outcomes can be said to be successful based on daily assessments and assignments that exceed the 7 mark which is the KKM according to the provisions.Keywodrs: Indonesian; digital; use of technologyPemanfaatan teknologi digital pada proses ajar-mengajar Bahasa Indonesia menjadi sesuatu yang nisbi saat ini. Artikel ini akan mendeskripsikan pemanfaatan, penggunaan, dan hasil belajar teknologi digital pada pembelajaran Bahasa Indonesia Kelas XI di SMA Muhammadiyah Al Mujahidin Wonosari. Jenis penelitian ini adalah deskriptif kualitatif. Subjek penelitian ini yaitu guru Bahasa Indonesia dan peserta didik. Teknik pengumpulan data berupa wawancara, observasi, angket, dan studi dokumentasi. Instrumen penelitian ini yaitu peneliti. Hasil penelitian ini adalah (1) pemanfaatan teknologi digital diterapkan dalam pembelajaranÂ khususnya pada materi karya ilmiah dan resensi mulai ketika memberikan pertanyaan pemantik, penyampaian materi, sampai pada penugasan serta penilaian harian (2)Â teknologi yang digunakan dalam penyampaian materi yaitu grup WhatsApp, Mentimeter, Youtube, Power Point (PPT), Google Forms, Portable Document Format (PDF), Internet, Microsoft Word, dan Random Team Generator (3) hasil belajar dapat dikatakan berhasil berdasarkan penilaian harian dan penugasan yang melampaui nilai 7 yang menjadi KKM sesuai ketentuan.Kata kunci: bahasa Indonesia; digital; pemanfaatan teknologi